Immunological considerations in the development of Pseudomonas aeruginosa vaccines. Issue 2 (1st February 2020) - Baker, Sarah M.; McLachlan, James B.; Morici, Lisa A.
ABSTRACT: Pseudomonas aeruginosa is an opportunistic human pathogen capable of causing a wide range of potentially life-threatening infections. With multidrug-resistant P. aeruginosa infections on the rise, the need for a rationally-designed vaccine against this pathogen is critical. A number of vaccine platforms have shown promising results in pre-clinical studies, but no vaccine has successfully advanced to licensure. Growing evidence suggests that an effective P. aeruginosa vaccine may require Th17-type CD4 + T cells to prevent infection. In this review, we summarize recent pre-clinical studies of P. aeruginosa vaccines, specifically focusing on those that induce Th17-type cellular immunity. We also highlight the importance of adjuvant selection and immunization route in vaccine design in order to target vaccine-induced immunity to infected tissues. Advances in cellular immunology and adjuvant biology may ultimately influence better P. aeruginosa vaccine platforms that can protect targeted human populations.